Tingkat Kualitas Pelayanan Kesehatan dalam Perspektif Islam dan Pengetahuan Pasien terhadap Penggunaan Antibiotik di RSI Sultan Agung Semarang - Ningrum, Yuyun Darma Ayu; Purnami, Islina Dwi; Virgianti, Mita (Sultan Agung Islamic University of Semarang, 2024)
Background: Hospital pharmacy services are a vital component of hospitals that contribute to the provision of high-quality healthcare. Infectious diseases are diseases caused by very dynamic pathogenic microbes, especially in developing countries. Therefore, antibiotics are drugs used for infections caused by bacteria. This research is aimed at determining the level of quality of health services from an Islamic perspective and patient knowledge about antibiotics. Methods: This type of research is quantitative research with descriptive methods. Meanwhile, the data collection technique used was using a questionnaire. Univariate analysis aims to explain or describe the characteristics of each research variable which generally only produces a frequency and percentage distribution of each variable. using a cross sectional descriptive method. Data is processed using the Statistical Product and Servicer Solution (SPSS) application. Results: The results of the research on the level of service quality according to the Islamic perspective for the five dimensions, namely Reliability as much as 64.4%, Responsiveness as much as 63.67%, Assurance as much as 36.67%, as much as 60.67% and Tangibles as much as 61.67% which falls into the sufficient category. , while the research results showed that the level of patient understanding regarding the use of antibiotics reached 56.43%, answering correctly, including in the correct category. Conclusion: There is a significant influence of knowledge regarding the level of health services and knowledge about the use of antibiotics, namely low.